2021
DOI: 10.52353/ama.v14i1.203
|View full text |Cite
|
Sign up to set email alerts
|

Perilaku Manajemen Keuangan Pada Umkm Sentra Kerajinan Kayu Di Kabupaten Dompu

Abstract: Latar Belakang: Perilaku manajemen keuangan menjadi salah satu konsep penting pada disiplin ilmu keuangan. Memiliki perilaku manajemen keuangan yang baik dapat membantu para pelaku UMKM untuk dapat bertanggung jawab dalam pengelolaan keuangan terhadap uang maupun asset dengan cara yang dianggap produktif. Tujuan: Untuk mengetahui Faktor-Faktor yang Mempengaruhi Perilaku Manajemen Keuangan pada UMKM Sentra Kerajinan Kayu di Kabupaten Dompu. Metode Penelitian: Penelitian ini merupakan penelitian yang bersifat ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
0
0
0
2
Order By: Relevance
“…Financial attitude refers to an individual's demeanor influencing their intent to achieve specific financial goals. It encompasses both informational and emotional aspects associated with the learning process, fostering a positive orientation toward financial actions, as Ariadin and Safitri (2021) noted. Additionally, Prihastuty and Rahayuningsih (2018) elaborate that financial attitude gauges an individual's psychological state when assessing financial management practices.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…Financial attitude refers to an individual's demeanor influencing their intent to achieve specific financial goals. It encompasses both informational and emotional aspects associated with the learning process, fostering a positive orientation toward financial actions, as Ariadin and Safitri (2021) noted. Additionally, Prihastuty and Rahayuningsih (2018) elaborate that financial attitude gauges an individual's psychological state when assessing financial management practices.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Previous studies have examined the impact of general financial attitudes on MSME financial management behavior, but their findings are diverse and inconsistent. While research by Kautsar et al (2020), Novianti and Salam (2021), Haqiqi and Pertiwi (2022), and Ariadin and Safitri (2021) have suggested a positive impact of financial attitudes on financial management behavior, studies by Aldiki et al (2022), Cahya et al (2021), andDesi (2022) have found no significant effect of financial attitudes on financial management behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian ini didukung pentingnya perilaku manajemen keuangan dalam disiplin ilmu keuangan (Ariadin, M., & Safitri, 2021). Perilaku tersebut membantu UMKM dalam mengelola keuangan secara produktif.…”
Section: Pendahuluanunclassified
“…The presence of inconsistencies in the results of previous studies. Financial management behavior is positively influenced by financial knowledge, financial attitudes, and personality (Humaira & Sagoro, 2018;Ariadin & Safitri, 2021). On the contrary, Estuti et al (2021) and also Ardhiyanti et al (2021), in the results of their research, found that there was no influence of financial knowledge on financial management behavior.…”
Section: Introductionmentioning
confidence: 99%